An experimental investigation of acoustic parameters of the laboratory for measuring sound insulation of building elements/Statinio elementų garso izoliacijai matuoti specialiai įrengtos laboratorijos akustinių parametrų tyrimas ir derinimas - Dikavičius, Vidmantas; Bliūdžius, Raimondas (Journal of Civil Engineering and Management, 2001)
The report deals with a task of investigating and adjusting acoustic parameters of the reverberant chambers of recently built laboratory for measuring sound insulation properties of building elements (windows, doors). The reverberation time values in the source and receiving empty rooms were measured at 16 one-third-octave frequency bands. It was determined that they significantly exceed the recommended ones. After a number of measurements the reverberation time was adjusted to the allowable limits. An optimum combination of loudspeaker positions in the source room with respect to the best acoustic field diffusivity has been experimentally found. Repeatability values r were calculated from the measurements of sound reduction index of plastic window conducted under repeatability conditions. At the 16 one-third-octave frequency bands they show a good precision of the test equipment.Article in Lithuanian.First Published Online: 30 Jul 2012